Pengaruh Pembiasaan Shalat Berjama’ah Terhadap Tingkat Kedisiplinan Siswa di Sekolah Menengah Pertama Negeri 1 Arosbaya - Istikmala hujjatulloh; Syahidah Rena (PGSD Universitas Muria Kudus, 2026)
This study aims to determine the effect of congregational prayer habituation on the level of student discipline at SMPN 1 Arosbaya. The research problem arises from the observation that some students show low discipline in obeying school regulations and inconsistency in participating in congregational prayers. This research employed a quantitative approach using a survey method with an associative research design. Data were collected through a structured questionnaire based on indicators of congregational prayer habituation and student discipline. The sample consisted of 154 students.Data were analyzed using simple linear regression to measure the influence of congregational prayer habituation on discipline. A normality test was conducted before regression analysis to ensure statistical assumptions were met. The results indicate that congregational prayer habituation has a positive and significant effect on student discipline, with a significance value of 0.000 < 0.05 and an F-value of 118.37. Descriptively, both variables were categorized as high. The highest habituation indicator was internalization of prayer, while the highest discipline indicator was compliance with school and home rules. Therefore, congregational prayer habituation can serve as an effective strategy in strengthening student character education, particularly in improving discipline.